Gricean Maxim Violation(s) in the Murder Case of Jamal Khashoggi: A Forensic Lingustic Perspective (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
The murder of Jamal Khashoggi in the consulate of Saudi Arabia in Turkey is still controversial. The judgment relies on valid and reliable evidence. This study is vital due to investigating a murder case based on pragmatic meanings as language evidence broadcasted in media. This research employs Grice’s conversational implicature to investigate the murder of Jamal Khashoggi by analyzing the exposed recorded tapes of Jamal Khashoggi and the accused inside the consulate, the utterances of Khadija Changiz, the fiancée of Jamal Khashoggi, and Adel al Jubeir’s statements, the foreign minister of Saudi Arabia as a representative of the Saudi Arabian. The design of this research is a case study, and content analysis is used to analyze the data based on Mayring’s (2000) qualitative content analysis. Based on the findings of the study, the recorded tapes of Jamal Khashoggi and the accused are outlined as ambiguous language. Saudi Arabia denied the murder by saving face, misleading the hearer, and skipping the questions, but later on, affirmed the murder and promised to bring justice. Hence, the results of this study will affect the verdict on the judicial decree, and the accusations will be prosecuted, and justice will be served to Jamal Khashoggi.